Radioactivity and Pollution in the Nordic Seas and Arctic Region Observations, Modeling, and Simulations - Johannessen, Ola M.; Volkov, Vladimir A.; Pettersson, Lasse H.; Maderich, Vladimir S.; Zheleznyak, Mark J.; Gao, Yongqi; Bobylev, Leonid P.; Stepanov, Andrey V.; Neelov, Ivan A.; Tishkov, Viktor P.; Nielsen, Sven P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
(3z(BPolar Seas Oceanography(3y (Bdescribes a new tool called the Generic Model System for simulations and assessment of potential radioactive spreading in the Arctic regions, through rivers, estuaries, regional seas and the Arctic and Atlantic basin. It considers the present and future potential for spreading of radionuclear pollution from sources, such as from the major Russian processing plants through Siberian rivers as well as from European sources such as the UK Sellafield plant. The book provides support for decision making involving risk prevention, forecasting and readiness for probable crises, alerting and detection, relief and mitigation and damage assessment. The book combines the expertise of professionals from the radionuclear and climate-change sciences.s
Sources of anthropogenic pollution in the Nordic Seas and Arctic -- Study region and environmental datasets -- Generic model system (GMS) for simulation of radioactive spread in the aquatic environment -- Studies of potential radioactive spread in the Nordic Seas and Arctic using the generic model system (GMS) -- Studies of the spread of non-radioactive pollutants in the Arctic using the generic model system (GMS) -- Assessment and input to risk management.
Keywords: Geography; Oceanography; Remote sensing; Earth Sciences; Earth Sciences, general; Oceanography; Remote Sensing/Photogrammetry.